Passive Transfer of Delayed Hypersensitivity to Blastomyces dermatitidis Between Mice - Scillian, James J. (1974)
This study further characterized the delayed hypersensitivity state induced in animals by Blastomyces dermatitidis exposure. Passive transfer of delayed hypersensitivity by transfer of cells and inhibition of migration of peritoneal exudate cells were studied, using sensitized mice of two inbred strains. Donor mice were subcutaneously inoculated with viable B. dermatitidis yeast cells. After 15 days, spleen cells or serum from these animals were injected intravenously into normal recipients of the same strain. After 24 h these mice were footpad tested with killed B. dermatitidis yeast cell antigen. Mice receiving spleen cells from sensitized animals had a significant increase in footpad thickness 24 to 48 h after testing. Those receiving only serum remained negative. Migration of peritoneal exudate cells from blastomyces-sensitive donor mice was inhibited by presence of blastomycin but not by mycobacterial antigen. Neither blastomyces-sensitive nor control animals reacted to footpad or migration inhibition testing with mycobacterial antigen.